Financial Capacity of Indonesian Schools and Community Learning Centers in Kota Kinabalu: A Comparative Analysis - Akadira, Tora (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to analyze the financial capacity of Indonesian Schools (SIKK) and Community Learning Centers (CLC) in Kota Kinabalu, focusing on the comparison of resources and financial management strategies. The research was motivated by the fundamental differences in access to and management of funds between these two types of educational institutions, which potentially impact the quality of education provided. A qualitative research approach was employed, with data collected through in-depth interviews, observations, and analysis of financial documents from SIKK and CLC. The data were analyzed using thematic analysis techniques to identify key patterns and differences in financial capacity between the two institutions. The findings reveal that SIKK has a more stable and structured financial capacity compared to CLC, which often faces uncertainties in funding. This instability is attributed to CLC's reliance on inconsistent funding sources, while SIKK benefits from greater government support. These findings highlight the need for a more sustainable and equitable funding model for CLCs to ensure their ability to provide quality education. The implications of this study suggest that improving financial capacity and better management in educational institutions can significantly impact the delivery of more equitable and high-quality education. Stakeholders, including the government and non-governmental organizations, should consider these recommendations in future educational policy planning.